Enhanced Photocurrent Generation in Proton‐Irradiated "Giant" CdSe/CdS Core/Shell Quantum Dots. (9th September 2019) - Wang, Chao; Barba, David; Selopal, Gurpreet S.; Zhao, Haiguang; Liu, Jiabin; Zhang, Hui; Sun, Shuhui; Rosei, Federico
Abstract: Group II–VI quantum dots (QDs) possess tunable electrical and optical properties that make them very attractive for high‐tech applications and power generation. The effects of proton irradiation on both the structural and physical properties of "giant" CdSe/CdS core–shell QDs (g‐CS QDs) are investigated. These experiments shed light on photoelectron delocalization in g‐CS QDs, where current linkages and strong variations in optical emission result from the spatial extension of the photoelectron wavefunctions over the conduction bands of CdSe and CdS. Monte Carlo simulations of ion–matter interactions show that the damaging rates can be set from the energy of impinging protons to promote the formation of structural defects in the core or shell. The formation of nanocavities is demonstrated after irradiation doses higher than ≈10 17 H + cm −2, while a continuous decrease in luminescence intensity is observed for increasing proton fluencies. This feature is accompanied by a concomitant lifetime decrease marking the rise of nonradiative phenomena and the occurrence of greater photocarrier transfers between CdS and CdSe. Current‐to‐voltage characterizations evidence that proton implantation can be implemented to enhance the photocurrent generation in g‐CS QDs. This increase is attributed to the delocalization of photoelectrons in the CdS shell, whose improvement is found to promote electron–hole pair separation. Abstract : The effects of proton irradiation on "giant" CdSe/CdS core/shell quantum dots (QDs) are reported. After irradiation, the formation of nanocavities is observed and both photoluminescence intensity and lifetime of QDs decrease with irradiation doses. The structural damage induced by proton bombardment is found to promote the photocurrent generation, which results from the occurrence of enhanced photoelectron delocalization in the CdS shell.